The Application of Big Data on The Performance of MSME Businesses in Batam City - Bahar, Hardi; Ayuningtyas, Ni Putu Winda; Lubis, Syarif Hidayah (Journal of Applied Business Administration, 2023)
This study investigates the influence of Big Data implementation on the business performance of Micro, Small, and Medium Enterprises (MSMEs) in Batam City. The research examines three characteristics of Big Data"”Data Volume, Data Velocity, and Data Variety"”and their impact on MSMEs' business performance. Data were collected through questionnaires distributed to MSME owners or managers in Batam. Statistical analysis, including descriptive statistics, validity tests, reliability tests, and hypothesis testing using T-tests, was conducted to analyze the data. The findings indicate that the implementation of Big Data with Data Volume and Data Velocity characteristics does not significantly influence the business performance of MSMEs in Batam City. However, the implementation of Big Data with Data Variety characteristics shows a significant positive influence on MSMEs' business performance. This suggests that the diverse information encompassed by Data Variety aids MSMEs in improving their business performance by identifying and addressing various aspects of their operations.